Protein Palmitoylation Modification During Viral Infection and Detection Methods of Palmitoylated Proteins - Li, Xiaoling; Shen, Lingyi; Xu, Zhao; Liu, Wei; Li, Aihua; Xu, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Protein palmitoylation—a lipid modification in which one or more cysteine thiols on a substrate protein are modified to form a thioester with a palmitoyl group—is a significant post-translational biological process that regulates the trafficking, subcellular localization, and stability of different proteins in cells. Since palmitoylation participates in various biological processes, it is related to the occurrence and development of multiple diseases. It has been well evidenced that the proteins whose functions are palmitoylation-dependent or are directly involved in the palmitoylation/depalmitoylation cycle of key proteins may be a potential source of novel therapeutic drugs for the related diseases. During viral infection, palmitoylation of proteins, which are crucial for host-virus interactions, has been reported by many researchers. Quite a few explorations have focused on figuring out whether targeting the acylation of viral or host proteins might be a strategy to combat viral diseases. All these remarkable achievements in protein palmitoylation have been made to technological advances. In this paper, we give an overview of protein palmitoylation modification during viral infection and the methods for palmitoylated protein detection. Future challenges and potential developments are proposed.